Export of Polish Machinery Industry to Türkiye 2015-2021: Case Study of Fan Factory (Politeja, 2025)
The article examines the dynamics of Polish machinery exports to Türkiye between 2015 and 2021, using Complex Interdependence Theory as the analytical framework. It highlights the historical, political, and economic context of Polish-Turkish relations, emphasising the role of non-state actors, trade institutions, and market mechanisms in shaping bilateral trade. Special attention is given to the case study of Fabryka Wentylatorów FAWENT S.A., a Polish industrial fan manufacturer, whose long-standing engagement with Turkish power plants and mines illustrates how industrial cooperation develops beyond traditional political or military concerns. The study demonstrates that despite geopolitical uncertainties and economic fluctuations, trade between Poland and Türkiye has shown resilience and potential for growth. The complementary industrial structures of both countries – particularly in the machinery, automotive, and energy sectors – facilitate mutual benefits and future opportunities for deepening cooperation. Findings confirm that Polish exports, driven by competitiveness and adaptability, are an important component of strengthening interdependence and expanding economic diplomacy in the Middle East region.